ANALISIS PENGARUH DISIPLIN DAN PROFESIONALISME PRAJURIT TERHADAP KINERJA LANAL MATARAM DALAM MELAKSANAKAN TUGAS OPERASI PERTAHANAN DAN KEAMANAN LAUT DI WILAYAH PERAIRAN NUSA TENGGARA BARAT - I GST GEDE NARUNG; I MADE MURJANA (GANEC SWARA, 2024)
This research is aim to analize the effect of work discipline and professionalism towards work performance of the Marine Corps in Lanal Mataram. The population of this research is 210 peaple and 42 people samples.This research using Questionaire technic as data collection method while SPSS application is required on data analysis. The result of this reserach shows 3 different hypothesis testing results. Based on first testing results indicates work discipline and professionalism simultanously give a of and significant effect towards the work performance of the Marine Corps in Lanal Mataram. The second testing shows work discipline partialy give a positive and significant effect towards the work performance, and the testing result show how profesionalism partialy effected the work performance in positive anf significant way.